National Adaptation Programmes of Action to Climate Change (NAPA) - Rwanda - Ministry of Lands, Environment, Forestry, Water and Mines (Ministry of Lands, Environment, Forestry, Water and Mines, 2006)
The NAPA Rwanda report is the result of a process of study, concertation and consultation carried out by NAPA national team from January 2005 to July 2006. Following directives of LEG – NAPA experts, the exercise aimed at evaluating current vulnerabilities to climate change according to the eight steps of NAPA guide in consideration of socioeconomic aspects and land use that exarcerbe these vulnerabilities, to identify most vulnerable population groups, regions and sectors, determine priority adaptation options, select urgent and immediate project activities to be implemented as well as defining their profiles.
Pages 85, with colored tables, graphs, maps. Includes references and annexes
Keywords: Climate Change